Structural changes in the cytoplasmic pore of the Kir1.1 channel during pHi-gating probed by FRET - Shieh Ru-Chi (Journal of Biomedical Science, 2009)
Abstract Kir1.1 channels are important in maintaining K+ homeostasis in the kidney. Intracellular acidification reversibly closes the Kir1.1 channel and thus decreases K+ secretion. In this study, we used Foster resonance energy transfer (FRET) to determine whether the conformation of the cytoplasmic pore changes in response to intracellular pH (pHi)-gating in Kir1.1 channels fused with enhanced cyan fluorescent protein (ECFP) and enhanced yellow fluorescent protein (EYFP) (ECFP-Kir1.1-EYFP). Because the fluorescence intensities of ECFP and EYFP were affected at pHi < 7.4 where pHi-gating occurs in the ECFP-Kir1.1-EYFP construct, we examined the FRET efficiencies of an ECFP-S219R-EYFP mutant, which is completed closed at pHi 7.4 and open at pHi 10.0. FRET efficiency was increased from 25% to 40% when the pHi was decreased from 10.0 to 7.4. These results suggest that the conformation of the cytoplasmic pore in the Kir1.1 channel changes in response to pHi gating such that the N- and C-termini move apart from each other at pHi 7.4, when the channel is open.